The Effects of Socio-demographic Characteristics on Indonesian Women's Knowledge of HIV/AIDS: A Cross-sectional Study - Putu Erma Pradnyani; Arief Wibowo; Mahmudah (Korean Society for Preventive Medicine, 2019)
Objectives The purpose of this study was to characterize Indonesian women's knowledge of HIV/AIDS and to investigate the effects of socio-demographic characteristics thereupon with the goal of supporting the prevention and early detection of HIV/AIDS. Methods This cross-sectional study was conducted using secondary data from the standard Indonesian Demographic and Health Survey (IDHS) in 2012. A total of 34 984 subjects ranged in age from 15 years to 49 years. Data were analyzed using the chi-square test and logistic regression to identify the effects of socio-demographic characteristics on Indonesian women's knowledge of HIV/AIDS. Results All socio-demographic characteristics except marital status were related to knowledge of HIV/AIDS among Indonesian women in the univariate analysis (p<0.05). Multivariate analysis revealed that only age group, education level, location of residence, and wealth index were related to Indonesian women's knowledge of HIV/AIDS (p<0.05). Conclusions Indonesian women's insufficient knowledge related to HIV/AIDS shows that the provision of accurate and comprehensive information related to HIV/AIDS are components of prevention and control interventions that should be improved. With greater knowledge, women are expected to be more likely to determine their own and their partners' human immunodeficiency virus status and to take appropriate preventive steps.